Crisis Management Board Game - Promsri, Chaiyaset; Chaigusin, Suchira (International Journal of Membrane Science and Technology, 2023)
This objective of study was to develop a crisis management board game for business organizations. This research used document analysis methods to study from two important sources: Devlin’s book Crisis Management Planning and Execution; an academic article titled “The Most Useful Crisis Management Examples: The Good, Bad, and Ugly” by Marker. The results demonstrated extracted lessons from five key scenarios, namely case studies of Tylenol, Union Carbide India, Mattel, Samsung, and Pepsi, which were used to formulate simulations and responses to each crisis situation. This board game was developed based on Dodge’s game design and development concepts, which clearly defines the elements in the development of a board game. However, the implementation should be done carefully in terms of the roles and responsibilities of personnel in each business organization. In addition, due to the situations created in this board game, all types of crisis may not be covered by these events. Therefore, further development of a crisis management board game with a variety of situations and scenarios is necessary for knowledge development and understanding of personnel in different types of organizations.